Noble gas isotope investigation of unconventional hydrocarbon reservoirs and related subsurface environments - Byrne, D (2018)
Unconventional petroleum reservoirs represent complex subsurface fluid environ- ments. Investigating the behaviour of these systems has important consequences for our energy production, environmental impact, and has the potential to further our general understanding of subsurface fluid behaviour in low-porosity systems. This study utilises noble gas isotopes in produced gases as geochemical tracers to investigate several facets of unconventional petroleum systems and related regimes. Firstly, the behaviour of source-rocks during natural gas generation is investigated in the Eagle Ford Shale (South Texas, USA). Here, clear relationships are shown between the noble gas composition and parameters for thermal maturity, including δ13C of methane. This allows new constraints to be placed on the behaviour of gas during generation and leads to novel approaches for quantifying the extent of gas generation within and expulsion from source-rocks. Secondly, the migration of hydrocarbons from source-rock to reservoir is investigated in a series of related samples from the Haynesville play area (East Texas, USA). Migrated samples from conventional reservoirs are shown to have much higher abundances of atmosphere- derived and radiogenic noble gas isotopes. These observations are used to test conceptual models of subsurface gas flow and ultimately to quantify the relative volumes of gas, water and rock encountered during migration. Finally, we investigate the behaviour of geothermal fluids in Iceland, using a similar approach but applying it to another low-porosity subsurface environment. Here, atmosphere-derived noble gas isotopes display solubility-dependent fractionation patterns, likely as a result of geothermal boiling and degassing at depth. The data and interpretations presented in this study greatly expand our understanding of noble gas behaviour in low-porosity rocks, and highlight new potential for their use as tracers in subsurface environments.